ANALISIS USER EXPERIANCE TERHADAP WEBSITE PERPUSTAKAAN UNIVERSITAS GUNADARMA DENGAN METODE HEURISTIC EVALUATION - Besty Ghina; Hafiz Ma'ruf; Jhordy Wong; Dewi Agushinta R.; Metty Mustikasari (Jurnal Ilmiah KOMPUTASI, 2019)
University of Gunadarma (UG) is a quite recognizable campus by the community as an IT-based campus. University of Gunadarma (UG) provides a library equipped with a variety of library materials consisting of literature books in both Indonesian and English, magazines, scientific journals, and other scientific books. Remote services are provided on this site to provide convenience for UG Library service users to increase knowledge. But there were still problems on the website display which needs to be repaired after interviewing 20 people who conducted a search of the UG library website. This study aims to evaluate the interface design of a website using human factors and ergonomic interpretation approaches to improve the usability and usefulness of a system display. The method used in this study is heuristic evaluation which has 10 well-known principle rules for evaluating an interface design. The results of the heuristic evaluation study generally showed an assessment of interface design, convenience, and user understanding of the UG Library website, that the results were unsatisfying with the research heuristic evaluation method. This is due to many dashboard navigations which not efficient and understandable. Many improved, especially things that contain characteristics on the ease of users to access will be needed.